Gosh- it was anxiety all along - Devaraj, Navin Kumar (DSR Publishers, 2021)
Psychological illness can present initially as physical symptoms and repeated request for medical leaves. It requires great clinical acumen to come to this often greatly elusive diagnosis. Thiswill include somatization disorder as one of the examples.This case reportson a 25-year-old woman with many physical symptoms and repeated requests for medical leave which was finally diagnosed as stress and anxiety.